(untitled) (Research, Society and Development, 2022)
Biotechnology has been an essential tool in the search for solutions and in the optimization of bioprocesses associated with issues of human, plant, animal, energy and also the balance of ecosystems on planet Earth. The objective of this research was to present an unconventional substrate (cellulose), in abundance on the planet, to be used as a substitute source of carbon and energy for biotechnology processes, with the possibility of increasing industrial production of biomass and energy. As basis for the research, an extensive literature review and quantitative and qualitative analyzes were carried out. Genetic Engineering techniques were used to enable the yeast Saccharomyces cerevisiae for partial cellulose degradation, through the use of genetic transformation methods to insert a plasmid carrying the cellobiohydrolase cDNA. It was found that the recombinant and biologically active cellobiohydrolase protein was expressed and excreted in haploid and diploid laboratory yeast strains. The analyzes allowed the visualization of cellulolysis halos around colonies of recombinant strains grown in solid YPD medium with 1% microgranular cellulose. The recombinant clones derived from the haploid lineage yielded in average of 1.70 mg ART/mL, while recombinant clones derived from the diploid lineage produced in average of 2.05 mg ART/mL.